Dynamics of Cognitive Impairment in Older Adults Linked to Suicide-Related Single-Nucleotide Polymorphisms: A 3-Year Follow-Up Study - Yana Zorkina; Alexander Berdalin; Irina Morozova; Alisa Andryushchenko; Konstantin Pavlov; Olga Pavlova; Olga Abramova; Valeriya Ushakova; Angelina Zeltzer; Marat Kurmishev; Victor Savilov; Olga Karpenko; et al. (Psychiatry International, 2025)
Background: Cognitive decline during aging is a factor that inevitably affects everyone. In some older adults, cognitive function declines more rapidly to mild cognitive impairment (MCI) and eventually dementia. Our work aimed to determine the associations between suicide-related single-nucleotide genetic polymorphisms (SNPs) and cognitive function dynamics in people over 65 years old over a three-year follow-up. Suicide-related SNPs have already shown an association with dementia in our previous study. Methods: The present study included 66 participants over 65 without subjective cognitive decline. Cognitive impairment was assessed at two follow-up points (at the start of the study in 2020–2021 and 3 years later) using the Montreal Cognitive Assessment (MoCA). Patients were also genotyped for 16 SNPs. Results: We found associations between rs10898553 and rs165774 and MoCA 3-year dynamics, with a certain genetic variant related to more significant progression. For rs7982251, associations with scale scores were found, but no effect on its dynamics. Conclusions: The research focused on analyzing genetic factors of cognitive decline in healthy older adults without subjective cognitive decline. Identifying these markers can help predict the development of pathology at early stages and start timely treatment.